Tool wear monitoring of high-speed broaching process with carbide tools to reduce production errors. (1st June 2022) - del Olmo, A.; López de Lacalle, L.N.; Martínez de Pissón, G.; Pérez-Salinas, C.; Ealo, J.A.; Sastoque, L.; Fernandes, M.H.
Graphical abstract: Highlights: An efficient monitoring method for high-speed broaching is presented. Time and Frequency domains signals are analyzed, taking into account the tooth passing frequency and harmonics. Tool wear is estimated in real-time, by monitoring process vibrations recorded by accelerometers. Experiments in nickel alloy type Inconel 718 (aged) pieces were carried out. Abstract: Real-time monitoring in CNC machine tools is focused on the early detection of tool wear, and in this way to assess part piece quality. The machining process known as broaching is critical for firtree slots (dovetails) production in turbomachinery components, such as turbine disks. Tight tolerances on one hand, even less than 5 µm in firtree-slots pressure faces, and high productivity on the other, are the two main requirements. Besides, broaching tools are very expensive and the cutting edges wear must be estimated during the process; in fact, tool wear in difficult-to-cut materials machining may cause a waste not only in terms of the tool but also of the very expensive workpieces. Broaching usually is one of the last operations in the process chain, so components start the operation with a very high-added value. Hence, only one bad slot implies an unrecoverable piece and therefore a huge waste of time and money. In this paper, a monitoring method for efficient broaching is proposed by combining real-time monitoring and off-line tool wear inspection. Firstly, the cutting tool characteristics are defined, and those affected by tool degradation. Secondly, some broaching cycles were carried out while measuring a) process accelerations through two accelerometers, b) cutting force by load cells, and c) motor drive consumption. They were simultaneously recorded. Furthermore, the sensitivity between tool wear and broaching process natural frequencies is established. Finally, a series of experimental tests were executed for verification, showing the useful approach for daily life production. The paper focuses on signals and their sensitivity to significant process variations.